Analgesic and Anti-Inflammatory Effects of Phaseolus vulgaris L. Fixed Oil in Rodents - Salma; Sadia Ghousia Baig; Muhammad Mohtasheem ul Hasan; Salman Ahmed; Syeda Anum Fatima (Journal of Basic & Applied Sciences, 2018)
The seeds of Phaseolus vulgaris are known as common beans or kidney beans. The dry seeds are eaten as pulse and are enriched with protein, fiber, starch, B vitamins (B1, B6, B9), iron, potassium and selenium. Beans also contain about 1-2 % of fixed oil. Phaseolus vulgaris is linked with anticancer, antihyperlipidemic, hypoglycemic and antioxidant actions. The fixed oil of Phaseolus vulgaris (PVFO) seeds is extracted with hexane and used in this study to assess acute oral toxicity, analgesic (by acetic acid induced writhing, hot plate and tail flick tests in mice) and anti-inflammatory (by carrageenan induced paw edema in rats) actions. Four groups were made (n=6): Group-I: Normal Saline Control (2ml/kg), Group-II: PVFO (2ml/kg), Group-III: PVFO (4ml/kg) and Group-IV: Standard Acetyl salicylic acid (ASA 300 mg/kg). PVFO in 2ml/kg and 4ml/kg dose demonstrated analgesic and anti-inflammatory activities but in hot plate results were unreliable as here significant activity started after 90 minutes. For toxicity test 5ml/kg dose was administered orally in mice and no toxicity symptoms were observed. It is therefore concluded that PVFO is safe for oral use up to 5ml/kg and may possess analgesic and anti-inflammatory actions.